Ethnic Disparities in Atherosclerotic Cardiovascular Disease Incidence and Prevalence Among Rheumatoid Arthritis Patients in the United States: a Systematic Review. Issue 9 (1st September 2020) - Daniel, Christina M.; Davila, Lesley; Makris, Una E.; Mayo, Helen; Caplan, Liron; Davis, Lisa; Solow, E. Blair
Abstract : Objective: Rheumatoid arthritis (RA) is associated with increased atherosclerotic cardiovascular disease (ASCVD). General population cohorts have shown African American individuals to have greater and Hispanic Americans to have lower cardiovascular disease prevalence when compared with non‐Hispanic white individuals; however, the reasons for these findings are not clear. This systematic review seeks to describe the incidence and prevalence of ASCVD stratified by race/ethnicity within the US RA population. Methods: MEDLINE, Embase, and Cochrane databases were searched for studies that reported incidence or prevalence of ASCVD (including, but not limited to, fatal and nonfatal stroke, myocardial infarction, and cardiovascular death) in those with RA. Abstracts and full texts were screened separately for inclusion by two reviewers, with a third reviewer to resolve discrepancies. Results: We screened 2625 abstracts and fully reviewed 138 manuscripts. Twenty‐one were included that cited at a minimum the percentage of non‐Hispanic whites in their population. No publication meeting entry criteria initially stratified ASCVD by race/ethnicity. The average prevalent ASCVD in RA is 46.9% (95% CI: 46.8–47) (range of prevalent ASCVD: 30%‐47%). The average incident ASCVD is 8.2% (95% CI: 8.14–8.25) (range of incident ASCVD 1%–46%). Conclusion: In this systematic review, we found a paucity of data on racially/ethnically diverse RA patients and ASCVD outcomes. Future studies should report the prevalence of ASCVD in various races/ethnicities with RA in the United States. These data would help inform clinicians on how best to manage cardiovascular disease risk in RA.